2020
DOI: 10.1088/2058-8585/abb931
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stretchable electronics made by fused-filament fabrication

Abstract: 3D printing is widely used for manufacturing complex non-functional parts, and recently, the fabrication of electronics has also attracted research attention. The commercialized process of fused-filament fabrication (FFF), which is still evolving,has been used in the preparation of basic electronic conductors and sensors but only a few studies of more complex structures with integrated circuits and passive components have been reported. Notably, the usage of FFF in wearable stretchable electronics has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…A TPU filament was used as a 3D-printed backbone for the fabricated structure. TPU is a widely used material in 3D printing and stretchable electronics because of its high deformability and stability [ 2 , 3 , 7 ]. For example, TPU-based stretchable films have also been used in wearable and printed electronics in combination with screen-printable conductive silver inks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A TPU filament was used as a 3D-printed backbone for the fabricated structure. TPU is a widely used material in 3D printing and stretchable electronics because of its high deformability and stability [ 2 , 3 , 7 ]. For example, TPU-based stretchable films have also been used in wearable and printed electronics in combination with screen-printable conductive silver inks.…”
Section: Methodsmentioning
confidence: 99%
“…FFF can also be adopted in the textile field by printing plastics directly on textile substrates [ 5 ] or by printing the whole textile composition [ 6 ]. Moreover, it has been demonstrated that FFF with deformable plastics and substrates can be used in manufacturing stretchable electronics, which can be further laminated on textiles for wearable electronics [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Screen-printing, inkjet printing, fused filament fabrication (FFF), and other additive manufacturing methods are used to fabricate deformable electronics [5,[10][11][12]. Inkjet printing is a widely used printing method for on-skin and wearable sensors and actuators [5,13].…”
Section: Printed Stretchable Electronicsmentioning
confidence: 99%
“…Besides other additive manufacturing methods, screen-printing is especially used in the fabrication of inherently deformable electronics for wearable applications [3,7,11,15]. In this case, the ink is squeezed through a screen onto a substrate, which enables the use of large conductive fillers and high polymer binder content in the inks [16].…”
Section: Printed Stretchable Electronicsmentioning
confidence: 99%
See 1 more Smart Citation